The Significance of Omnibus Law Technique to Indonesia’s Law Making: How it Started and Would Evolve - Sjarif, Fitriani Ahlan (VNU Journal of Science: Legal Studies, 2025)
: Indonesia’s omnibus highlights the drafting technique’s importance and development. In pursuit of addressing the bureaucratic burden and proliferation of overlapping regulations, the Government of Indonesia introduced the omnibus drafting technique, a way of amending multiple laws within a single law, and the first of its kind in Indonesia. The first omnibus law in Indonesia was followed by public outrage because it contained unpopular provisions, did not comply with drafting techniques, and did not satisfy public participation standards. The omnibus law technique had not been adopted to the official Guide of Legislative Drafting when the law was made. In the next development, other omnibus laws on health and financial agencies were enacted. Each of them has its unique features. Omnibus Job Creation Law and the omnibus technique do actually affect the legislative drafting style in Indonesia’s recent lawmaking practices, namely the amendment style and the importance of public participation given omnibus’s massive size. Therefore, it is worth pausing to visit the initial development of the omnibus law in Indonesia while also foreseeing how it would affect drafting style and evolve.